The effectiveness of cybertherapy for the introvert and extrovert personality traits - Zainudin, Zaida Nor; Mohamad Yusop, Yusni; Hassan, Siti Aishah; Alias, Bity Salwana (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: The cyberspace creates an infrastructure to build relationships, so the counseling practitioners has taken the initiative to maximize their services. An alternative service helps through this virtual interaction is created and practised. This virtual counselling service is known as cyber-counselling. So, there is a need to see the effectiveness of this cybertherapy service based on personality traits. The objectives of this study are to see the relationships or differences between personality trait in cyber-counselling approach. Methods: This quasi-experimental research applied the Non-Equivalent Pre & Post Test design. 60 research subjects are identifed and divided into the two groups the Face-to-Face approach and Cyber-counselling approach. Junior Eyneseck Personality Inventory was used to determined their personality traits and Client Satisfaction Inventory to determine the effectiveness of the therapy. Results: Pearson Chi-Square test shows that client satisfaction has no relationship on personality traits towards cybertherapy approach. Conclusion: Since the findings of this study are not in line with past literatures, some assumptions can be made regarding the findings of this study. Firstly, the distribution of the subjects based on personality traits can not be done in view of the ‘walk-in’ elements practiced in this study. Secondly, since the subjects are within the age of 13 to 17 years, the likelihood of the formation and development of their personality traits has yet to mature or steady, while the previous studies conducted on the study of adults.